2020
DOI: 10.1371/journal.pone.0227686
|View full text |Cite
|
Sign up to set email alerts
|

Transforming assessment of speech in children with cleft palate via online crowdsourcing

Abstract: Speech intelligibility is fundamental to social interactions and a critical surgical outcome in patients with cleft palate. Online crowdsourcing is a burgeoning technology, with potential to mitigate the burden of limited accessibility to speech-language-pathologists (SLPs). This pilot study investigates the concordance of online crowdsourced evaluations of hypernasality with SLP ratings of children with cleft palate. Methods Six audio-phrases each from children with cleft palate were assessed by online crowds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Forty-five articles were ultimately included for data extraction (Table 1). 13–57 Proportionate rater agreement was 91.7% for abstract screening and 92.5% for full-text screening. The Cohen kappa coefficient for interrater reliability was 0.82 for abstract screening and 0.81 for full-text screening, demonstrating sufficient interrater reliability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-five articles were ultimately included for data extraction (Table 1). 13–57 Proportionate rater agreement was 91.7% for abstract screening and 92.5% for full-text screening. The Cohen kappa coefficient for interrater reliability was 0.82 for abstract screening and 0.81 for full-text screening, demonstrating sufficient interrater reliability.…”
Section: Resultsmentioning
confidence: 99%
“…We identified seven studies making these comparisons within our own specialty, the concordances between groups being quite variable (Table 5). It is paradoxical that the degree of complexity or sophistication of the topic does not seem to predict the agreement of layperson and experts; for example, crowds were found to agree with experts on ratings of hypernasal speech, 44 but disagree on a five-option comparison of eyelid swelling 43 or the aesthetics of umbilicoplasty. 52 Because the number of studies evaluating these comparisons is quite small, more studies are needed to determine the areas in which crowds may provide expert-level comparable ratings.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, crowdsourcing has been successfully used in medicine, 15,16 including the evaluation of surgical skill, 17 detection of abnormality, 18–20 and assessment of patient perspectives on health care. 21 More recently, crowdsourcing’s applications have spread to plastic surgery and cleft outcomes, with applications in cleft speech, 8 lip appearance, 9 and orthognathic surgery results. 22 This article represents a novel approach in multiple aspects, not only for its direct evaluation of the relative importance of scar severity versus Cupid’s bow peak angle, but in its approach to cleft outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Online crowdsourcing is a burgeoning technology that allows researchers to leverage large-scale opinions of the general public. Platforms such as Amazon Mechanical Turk (MTurk), have previously investigated the concordance of layperson crowdsourced worker ratings with ratings of experts in the domains of cleft speech and Asher-McDade fixed-scale ratings, [8][9][10] and used MTurk to compare aesthetic outcomes in cleft lip repair. 11,12 Encouraged by the results of these studies, which found that online crowdsourced ratings are highly consistent with expert opinion, we aim to understand lay perspective of cleft outcomes using a novel technique of simulating different lip angles and scar thicknesses.…”
mentioning
confidence: 99%
“…Finally, it is important to note that there is burgeoning interest in using new technologies to evaluate CP outcomes, such as virtual crowdsourcing and deep learning algo-rithms. [31][32][33][34] Once established, these strategies could be quickly adopted on a global scale and used in low-resource areas to help alleviate disparities in cleft care.…”
Section: Discussionmentioning
confidence: 99%